PERAN INDONESIA DALAM PENANGGULANGAN NARKOTIKA - Zaidan, M Ali; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2015)
Narcotics is an international problem faced  by the nations of the world.  Narcotic crime is a crime that is extra ordinary crime and has become transnational organized crime. Therefore its eradication must be carried out with  the  cooperation  of  each  country while effecting the respective national laws in addition  adopt  a  international conventions relating to counter-narcotics. Indonesia's role occupied a strategic place, especially in Southeast Asia and the world at large. Indonesia has shown firmness in the form of legislation that threatens the maximum punishment and they are proven to distribute narcotics have been partially executed. Indonesia is responsible at least in the region makes the drug as a common enemy .